Diseño de un plan de supervisión para la aplicación del check-list de cirugía segura: una revisión sistemática - Nole Zhingre, Brandon Eduardo (2026)
The Safe Surgery Checklist (SSC) is a tool developed by the World Health Organization to reduce complications and mortality associated with surgical procedures. Factors such as work overload, organizational limitations, and lack of rigorous monitoring negatively affect the full implementation of the protocol. The overall objective of the research is to analyze the degree of adherence to the SSC, using recent scientific evidence to describe its implementation in various hospital settings. The methodology adopted followed the PRISMA guidelines. Searches were conducted in indexed databases such as PubMed, SciELO, Scientific Reports, Dialnet, ScienceDirect, Elsevier, and Google Scholar during the years 2019-2025. The main results indicate that, despite the high level of theoretical knowledge about the LVCS and its recognized potential to improve patient safety, it is imperative to implement strategies for continuous training, effective leadership, and periodic audits, which allow for the systematic integration of the checklist into clinical practice and, in this way, optimize patient safety outcomes.